Care for Joy: Evaluation of a Humor Intervention and Its Effects on Stress, Flow Experience, Work Enjoyment, and Meaningfulness of Work - Bartzik, Marek; Bentrup, Andreas; Hill, Susanne; Bley, Maria; von Hirschhausen, Eckart; Krause, Gerrit; Ahaus, Peter; Dahl-Dichmann, Angelika; Peifer, Corinna (Frontiers in Public Health, 2021)
The media increasingly speak of a care crisis. Systematic support is needed to prepare nursing apprentices for the high demands of their profession and to reduce the number of people quitting it. Particularly in stressful jobs like nursing, humor as a coping strategy can have a beneficial effect on perceived stress and the overall work enjoyment. In this study, we used a humor intervention among nursing staff in training and evaluated its effects on humor, stress, work enjoyment, the meaningfulness of work and flow experience. The sample consists of 104 nurses in training. The intervention group received a three-hour humor intervention, while the control group received no intervention. Positive and negative affect were measured immediately before and after the intervention. Humor was measured before the intervention (t0) and 6 months later (t1); at t1, we again measured stress, work meaningfulness, work enjoyment, and flow experience. Our analyses showed a beneficial change in positive and negative affect right after the intervention. By means of ANOVA we could further confirm an effect of the intervention on reported humor 6 months later. Humor mediated positive effects of the humor intervention on perceived meaningfulness of work, work enjoyment, and on the frequency of flow at work. Also, we found a significant negative relationship between humor and stress measured at t1. The results of this study confirm the effectiveness of humor intervention in promoting humor, and through this, the meaningfulness of work, work enjoyment, and the frequency of flow experience. Implications for the use of humor interventions in the nursing profession are discussed.